Continuing and Coordinating Care in Communities of Chronic Illness by using WHO Concept of Integrated Centered Health Services in Thailand and Indonesia - Artsanthia, Jintana; Rungrojwattana, Wassana; Putu Darma Suyasa, I Gede; Swarjana, I Ketut (Journal of The Royal Thai Army Nurses, 2023)
A sequential explanatory design of mixed-method research explored continuing and coordinating care in communities of chronic illness by utilizing the World Health Organization (WHO) concept of centered patient healthcare services and to stimulate a strong community for sustainable and equilibrium of continuing and coordination of care. The target population was people with chronic illness and healthcare professionals, 160 samples came from 80 of each site. Each site was composed of 50 Participants with chronic illnesses and 30 people were representing community healthcare providers. Data collection and analysis started with quantitative data, then qualitative data in a second phase. The questionnaires for patients and healthcare providers were proposed to3 expertise for content validity was .96 and reliability for Cronbach’s Alpha at .98, .87 respectively. The content of the collected data was analyzed 1) in quantitative data; descriptive analysis; 2) Content analysis was used in qualitative data. Quantitative research results showed that continuing and coordination of care in Thailand and Indonesia were composed following 1. Continuing with a primary care professional had an average score of 3.82 ± .74 vs. 4.15 ± .83, 2) Collaboration in care and sharing decision-making scored on average 3.84 ± .79 and 4.25 ±.75, 3) Case management with complex needs was rated at 3.83 ± .75 compared to 4.21 ± .74 ; 4) Collocated services of access were rated at 3.67 ± .87 compared to 4.23 ±.74 5)Transitional or intermediate care had an average score of 3.66 ±1.48 vs. 4.16 ± .73, 6) Comprehensive care along the entire pathway had an average score of 3.78 ± .78 vs. 4.20 ± .78, 7) Technology in continuity and coordination of care had an average score at 3.54 ± .86 vs. 4.24 ± .74, 8) Building workforce capability had an average score at 3.76 ± .84 vs. 4.24 ± .74. Qualitative Research results showed the strengthened community for sustainability and equilibrium of continuing and coordination of care found that the system of caring was well-organized top to bottom and bottom to top, health volunteers with a high level of spirit, and a budget was to support the system. It can be concluded that continuing and coordinating care in the community should have good systems, good organizations, financial support, the spirit of healthcare providers and the use of technology to provide information supporting care will increase sustainable programs for patients’ satisfaction and wellbeing. Moreover, the WHO concept of integrated health services will guide the healthcare providers to awareness to create a sustainable quality of life in the community.